Biology of subterranean populations of woolly apple aphid, Eriosoma lanigerum (Hausmann)(Homoptera:Aphididae), in apple orchards - Damavandian, M. R. (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD (Agric))--University of Stellenbosch, 2000.